Peran Pendidikan Islam Dalam Membentuk Karakter Siswa - Andri Setiadi; Aulia Naufal (Rayah Al-Islam, 2025)
Islamic education has an important role in shaping the character of students by instilling moral and spiritual values that can form good attitudes and behaviors in daily life. However, in its implementation, Islamic education faces various challenges, such as the lack of quality of human resources (teachers), difficulties in integrating theory with practice, and the influence of outside cultures that can affect the values taught. This study aims to analyze the role of Islamic education in shaping the character of students, evaluate effective learning methods, and identify challenges faced in its implementation. The method used is a qualitative method, data sources are obtained from various documents relevant to the study, data analysis techniques use descriptive analysis techniques. The results of the study show that Islamic education is effective in shaping the character of students, but it needs to be improved in teacher training and adjustment of learning methods to be more relevant to the times. Islamic education must better integrate technology in the learning process to increase its effectiveness. In conclusion, Islamic education has great potential in shaping the character of students, but it is necessary to innovate and strengthen its implementation.